2015
DOI: 10.1002/hipo.22500
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive state following mild stroke: A matter of hippocampal mean diffusivity

Abstract: The hippocampus is known to play a vital role in learning and memory and was demonstrated as an early imaging marker for Alzheimer's disease (AD). However, its role as a predictor for mild cognitive impairment and dementia following stroke is unclear. The main purpose of this study was to examine the associations between hippocampal volume, mean diffusivity (MD) and connectivity and cognitive state following stroke. Eighty three consecutive first ever mild to moderate stroke or transient ischemic attack (TIA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…The meta-analysis by Clerx et al (Clerx, et al, 2012) of 55 DTI studies comprising 2,791 individuals has shown that the effect sizes of hippocampus MD are larger than those for hippocampus volume when predicting individuals with MCI (Clerx, et al, 2012). Similar conclusions have been made with respect to stroke patients (Kliper, et al, 2016), and to Parkinson’s disease (PD), where again hippocampus MD better predicts memory scores in PD patients (Carlesimo, et al, 2010). In terms of other regions, putamen MD is another good discriminator of individuals who develop PD (Peran, et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The meta-analysis by Clerx et al (Clerx, et al, 2012) of 55 DTI studies comprising 2,791 individuals has shown that the effect sizes of hippocampus MD are larger than those for hippocampus volume when predicting individuals with MCI (Clerx, et al, 2012). Similar conclusions have been made with respect to stroke patients (Kliper, et al, 2016), and to Parkinson’s disease (PD), where again hippocampus MD better predicts memory scores in PD patients (Carlesimo, et al, 2010). In terms of other regions, putamen MD is another good discriminator of individuals who develop PD (Peran, et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…Among reports investigating the strength of association between volume and MD at subcortical ROIs, most have focused on mild cognitive impairment (Fellgiebel and Yakushev, 2011; Muller, et al, 2007), Alzheimer’s disease (Cherubini, et al, 2010; Kantarci, et al, 2005), and stroke (Kliper, et al, 2015). Two studies, each based on small case-control designs (Kantarci, et al, 2005; Kliper, et al, 2015), have reported large significant correlations between hippocampus volume and MD. In contrast, one report based on a large sample of elderly, non-demented subjects by den Heijer et al (den Heijer, et al, 2012) found no correlation between hippocampus volume and MD.…”
Section: Introductionmentioning
confidence: 99%
“…Results from the SMART-MR study suggested that the interaction between brain atrophy and white matter hyperintensities or infarcts could aggravate cognitive decline [75]. There is evidence of the role of hippocampal mean diffusivity in the post-stroke cognitive state, above and beyond that of volume and connectivity of this structure [76]. …”
Section: Neuroimagingmentioning
confidence: 99%
“…7 Similarly, changes in hippocampal mean diffusivity and hippocampal connectivity predict cognitive state at 6 and 12 months after a mild stroke. 8 Structural and functional changes, including these subtle changes to hippocampal shape and texture, atrophy in areas outside of hippocampus, and disruption to functional networks are also seen in the course of Alzheimer disease, 9 suggesting that TIA or minor stroke possibly induce a long-term neurodegenerative process.…”
Section: See Related Article P 384mentioning
confidence: 99%